An afferent pathway for the selective release of vasopressin in response to carotid occlusion and haemorrhage in the cat - Clark, Barbara J. (1967)
1. The release of neurohypophysial hormones in response to carotid occlusion and haemorrhage has been studied in anaesthetized cats. Samples of jugular venous blood were extracted with alcohol and the extracts assayed for antidiuretic and milk-ejecting activity. 2. The release of vasopressin in response to bilateral occlusion of the common carotid arteries has been confirmed in the cat; this effect was abolished when the sinus nerves were divided. 3. Using a new sensitive preparation for the assay of milk-ejecting activity in blood extracts, it has been shown that no oxytocin accompanies the release of vasopressin during carotid occlusion. 4. The independent release of vasopressin without oxytocin during haemorrhage has also been confirmed, and the role of the sinus nerves and vagi in this response investigated. Bilateral division of either nerve reduced the response, but the vagus appeared to be of greater importance than the sinus nerve. 5. A reflex arc for the selective release of vasopressin has been proposed, of which the fibres of the sinus nerves and vagi form the afferent component and the neurones of the supraoptic nucleus the efferent component.